2013
DOI: 10.1161/strokeaha.113.001538
|View full text |Cite
|
Sign up to set email alerts
|

Physical Activity Frequency and Risk of Incident Stroke in a National US Study of Blacks and Whites

Abstract: Background and Purpose Regular physical activity is an important recommendation for stroke prevention. We compared the associations of self-reported physical activity (PA) with incident stroke in the REasons for Geographic And Racial Differences in Stroke (REGARDS) study. Methods REGARDS recruited 30,239 US blacks (42%) and whites, aged ≥45 with follow-up every six months for stroke events. Excluding those with prior stroke, analysis involved27,348participants who reported their frequency of moderate-vigorou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
67
1
1

Year Published

2014
2014
2022
2022

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 104 publications
(73 citation statements)
references
References 33 publications
4
67
1
1
Order By: Relevance
“…However, our study from representative population‐based cohort data showed no significant effect modification by sex, which is consistent with the recent meta‐analysis 19. Another interesting point was that participants with older age or more vascular risk factors performed the highest frequency of MVPA, which is different from the previous results of Western countries 20, 21. Although MVPA had a similar degree of effect on the risk of an ischemic stroke and an intracerebral hemorrhage (20% versus 15% lower risk, respectively), the association was significant in an ischemic stroke, but not in an intracerebral hemorrhage.…”
Section: Discussionsupporting
confidence: 80%
“…However, our study from representative population‐based cohort data showed no significant effect modification by sex, which is consistent with the recent meta‐analysis 19. Another interesting point was that participants with older age or more vascular risk factors performed the highest frequency of MVPA, which is different from the previous results of Western countries 20, 21. Although MVPA had a similar degree of effect on the risk of an ischemic stroke and an intracerebral hemorrhage (20% versus 15% lower risk, respectively), the association was significant in an ischemic stroke, but not in an intracerebral hemorrhage.…”
Section: Discussionsupporting
confidence: 80%
“…Although this study's findings could not establish a causal relationship between breastfeeding and risk of stroke, health disparities surrounding stroke1, 5, 6, 7, 8, 9, 10, 11, 12, 13, 14, 15, 16, 17, 18 and breastfeeding rates52, 53, 54 persist. Stroke is 1 of the leading causes of death among Hispanic and non‐Hispanic black women over 65 2, 4.…”
Section: Discussioncontrasting
confidence: 63%
“…Stroke costs the nation $34 billion annually including the cost of healthcare services, medications, and lost productivity 1. Approximately 55 000 more US women than men suffer from a stroke annually 1, 5, 6, 7, 8, 9, 10, 11, 12, 13, 14, 15, 16. Compared with elderly men, elderly female stroke survivors are also at increased risk for moderate to severe disability, poorer quality of life, and institutionalization 16, 17…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In addition, it appears that physical activity can also decrease stroke in primary prevention studies. 44,87 A 2010 meta-analysis demonstrated that an increased level of physical activity has the potential to reduce stroke incidence and stroke-related outcomes.…”
Section: Physical Activitymentioning
confidence: 99%